Upaya Meningkatkan Pemahaman Siswa Tentang Bahaya Bullying Melalui Layanan Bimbingan Klasikal Pada Siswa Kelas VIII di SMPN 1 Sungai Pua - Haulia Tris Finanda; Hidayani Syam (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Bullying is very common in the school environment because it can disrupt students' learning at school. Schools, especially guidance and counseling teachers, have an important role in ensuring that students or students avoid bullying so that they are able to learn effectively and efficiently. Students who have an understanding of the dangers of bullying will have a greater opportunity to avoid levels of bullying and understand the dangers of bullying. This research also aims to ensure that students can find out that there is an increase in understanding of the dangers of bullying through classical guidance for class VIII students at SMPN 1 Sungai Pua for the 2023/2024 academic year. This research shows that after being given classical guidance services, more than half of the students can understand the dangers of being in the very high category. In the high category with a frequency of 6 it was 18.75%, in the medium category the frequency of 3 was 9.375%, in the low category the number of 0 was 0%, in the very low category with a frequency of 0 it was 0%. Thus, it can be concluded that classical guidance is an effective and innovative strategy to increase the understanding of class VIII students at SMPN 1 Sungai Pua regarding the dangers of bullying. The results of this research can be used as reference material for guidance and counseling teachers to increase understanding of the dangers of bullying in students through classical guidance services.